(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article reveals specific aspects of mythology in modern communicative practice. In addition, the philosophical features of mythology related to language have been interpreted. The content and essence of mythology have also been revealed by philosophers from a modern point of view. Again, aspects of mythology related to language, logos, nature, and man of modern philosophy are revealed.